Small Cell Deployment and Smart Cooperation Scheme in Dual-Layer Wireless Networks. (19th March 2014) - Wei, Su; Qi, Liu; Yiqun, Li; Meng, Bi; Guoli, Chen; Hongke, Zhang
Abstract : Traditional mobile networks will become dual-layer wireless networks due to small cells' deployment. The advantages of dual-layer networks are improving network capacity and overcoming the problem of unbalanced traffic distribution in time-space domain. In this paper, performance of small cells deployment is evaluated in simulations. It is shown that users' traffic is offloaded by small cells obviously. At the same time, performances of signal to interference plus noise ratio (SINR) and throughput are also improved. However, low SINR (SINR < 10 dB) users are also increased because of interferences between macro cells and small cells. Furthermore, a new cooperation scheme is proposed for energy saving in dual-layer networks. This scheme is implemented through a functional modular, named by Area Control Center (ACC). Finally, simulations are given to verify the efficiency of this energy saving scheme. The numerical results show that energy consumption could be reduced by 20%.